An in vitro study on the effectivity of "vitamin c" from guava (Psidium guajava) as tooth whitening agent on bovine teeth - Pitero, Karen Grace A.
This study was aimed to determine the effectiveness of Vitamin C in guava as a whitening agent as well as to determine if there is possible loss of tooth structure after the whitening process. Guava fruits were collected and processed to create the bleaching solution. One hundred freshly extracted bovine teeth were cleansed and stored in saline solution prior to exposure to the bleaching solution. The bovine teeth were randomly grouped into five namely; CG n as the control group, RSI as the twenty bovine teeth exposed to 0.128% concentration of the whitening solution for 30 minutes, RS2 as the twenty bovine teeth exposed to 0.128% concentration of the whitening solution for one hour, rsl as the twenty bovine teeth exposed to 0.064% concentration of the whitening solution for 30 minutes, and rs2 as the twenty bovine teeth exposed to 0.064% concentration of the whitening solution for one hour. Baseline shade and weight determination were done accordingly. The specimen were then stored in artificial saliva a day before they were subjected to the whitening solution as per their treatment groups. The shade of each specimen was assessed on the third, sixth and ninth day. Weight for each specimen after the whitening treatment process was recorded (with and without label). Statistical Analysis using Tukey test [P< 0.05] and Analysis of Variance - two factorial design [P< 0.05], and line graph were done. Group RSI, rsl and rs2 were deemed effective since whitening was observed up to seven, four, and five shades respectively and there is no significant difference in the weights of the bovine teeth before and after treatment. RS2 group, having a higher concentration (.128%) with a longer immersion time of one hour, produced the most effective whitening results with up to 9 shades lighter. It is concluded that Vitamin C from guava is an effective whitening agent.